Apuntes sobre el derecho del ciudadano a informarse de lo que sucede en la Administración Pública - Orrego Azula, Cesár Augusto (Revista de Derecho, 2019)
We are finishing the first decade of the new millennium, which has brought with it structural changes in the world and in Peru. Our country faced the need to re-take the road towards democracy, in a transition which started with the late President Paniagua Corazao and which has posed a succession in power of two democratically elected presidents. This road which by no means is free from great challenges and difficulties has been illuminated by a norm of indispensable and unquestionable democratizing value, the Law of Transparency and Access to Public Information, which has at is heart the aim of printing in Peruvian society a new relationship process between the citizen and the State, guided by the principle of publicity of public acts and in this way the result from the work done by the civil society, the media, the Constitutional Tribunal and the Ombudsman’s Office; among other institutions which are fostering the real validity of the fundamental right regulated in the 2 article clause 5 of the Peruvian Constitution has been outstanding.
Keywords: Access to information; democracy; publicity; cost of reproduction; transparency law; deadlines; Habeas Data